2015
DOI: 10.1002/brb3.296
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pain in amyotrophic lateral sclerosis

Abstract: BackgroundPain is an often underestimated and neglected symptom in amyotrophic lateral sclerosis (ALS).MethodsIn a cross-sectional survey, 46 patients with ALS, 46 age- and gender matched population-based controls, and 23 diseased controls with myotonic dystrophy type 2 (DM2) were screened for occurrence, type, distribution, and treatment of pain and cramps. Data were collected with the use of the short form brief pain inventory (BPI).ResultsPain was reported in 78% of ALS patients,79% of DM2 patients, and 54%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
2
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(105 citation statements)
references
References 26 publications
10
87
2
6
Order By: Relevance
“…Pain in our series was, on average, moderate in intensity, but was severe in some patients, and a barrier to daily life activities. Similar findings have been observed by others (2,3,6) and by us in a previous series of patients recruited by a different method (23). Importantly, relief as a result of pain treatments was not impressive, averaging less than 50% (100% ¼ complete relief).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Pain in our series was, on average, moderate in intensity, but was severe in some patients, and a barrier to daily life activities. Similar findings have been observed by others (2,3,6) and by us in a previous series of patients recruited by a different method (23). Importantly, relief as a result of pain treatments was not impressive, averaging less than 50% (100% ¼ complete relief).…”
Section: Discussionsupporting
confidence: 90%
“…Nearly a quarter of the sample experienced no pain relief, and this is a major concern. Others have found that the use of opioids is common, yet those same series demonstrate significant average pain (2,3,6). It is unknown whether the poor pain control is due to lack of adequate assessment of pain by the health care team, ineffective treatments, or other causes, but it certainly is meaningful that almost 30% of our study patients were not receiving any treatment for their pain.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Approximately half of the ALS patients used more than five CAM in a Chinese study [19]. Additionally, three studies undertaken in Germany and China identified most ALS patients as concurrently using CAM alongside riluzole [18][19][20].…”
Section: Prevalence Of Cam Use In Alsmentioning
confidence: 99%
“…Concerning the relief of ALS symptoms via CAM use, magnesium and acupuncture/massage therapy have been used for the management of ALS-related cramps and pain, respectively [20], and Chinese medicine was found to be used for weakness and fatigue, muscle atrophy, and/or limb pain [19].…”
Section: Decision-making For Cam Use In Alsmentioning
confidence: 99%